Continuous product innovation - learning behaviours and knowledge management. (1st January 2002) - Gieskes, Jose F.B.; Hyland, Paul W.; Chapman, Ross
The research reported in this paper considers Product Innovation from a broader perspective than that of the isolated NPD (New Product Development) project commonly discussed in the literature. In this perspective, Product Innovation is a continuous and cross-functional process involving the sharing and transfer of knowledge within the many steps of the innovation process, and the integration of a growing number of different competencies inside and outside the organisational boundaries. This paper examines two in-depth case studies that were carried out to establish if and how learning occurred within companies developing new products. Based on a model developed as part of a joint Euro-Australian research project, the way in which the selected companies share and transfer knowledge and learning experiences during their product innovation processes have been examined and analysed. This model uses a number of interrelated variables including performance, behaviours and levers to stimulate improvement, contingencies, and learning/innovation capabilities to describe the learning and knowledge transfer in product innovation processes within the case studies. This paper discusses some of the skills the research has identified that managers need to enable their companies to gain a competitive advantage through improved product innovation. The ongoing research has developed, tested and disseminated a computer-based methodology to assess organisational knowledge capture and transfer in the new product development process. The research is part of the Euro-Australian co-operation project known as CIMA (Continuous Improvement and Product Innovation Management).